Using proton pump inhibitors increases the risk of hepato-biliary-pancreatic cancer. A systematic review and meta-analysis - Zhou, Wence; Chen, Xinlong; Fan, Qigang; Yu, Haichuan; Jiang, Wenkai (Frontiers in Pharmacology, 2022)
Background: For the past two decades, dispute on whether proton pump inhibitor (PPI) leads to malignant tumors remains, emerging studies still demonstrate inconsistent results, which continues to perpetuate concerns over the safety of PPI use. So we performed a systematic review and meta-analysis to assess the effect of PPI use on Hepato-biliary-pancreatic cancer. Methods: For this Meta-analysis, PubMed, EMBASE, and Web of Science were searched up to July 1, 2022, 23 studies (16 case-control and 7 cohort studies; 257, 6791 individuals) included in this study. Pooled odd risks (ORs) were estimated via random effects models. We also conducted sensitivity analysis and dose-response analysis, subgroup analysis. Results: The pooled OR of the meta-analysis was 1.69 (95% Confidence interval (CI): 1.23–2.22, P = 0.01), with a substantial heterogeneity (I2 = 98.9%, P< 0.001). Even when studies were excluded one by one, the pooled OR remained statistically significant. According to the stratified subgroup analyses, Hepato-biliary-pancreatic cancer incidence was positively associated, regardless of the study design, quality of studies, and country. The association between PPI and hepato-pancreatic cancer is stronger in people with minimal exposure. When cumulative defined daily dose increases, the risks decline and become non-significant. But the results of the biliary tract cancer analysis do not seem to be the same, and there is an association between a higher level of PPI use and biliary tract cancer. Conclusion: PPI use may be associated with the increased risk of Hepato-biliary-pancreatic cancer. Hence, caution is needed when using PPIs among patients with a high risk of Hepato-biliary-pancreatic cancer.